Exposure risks to carcinogens in food: formation of heterocyclic aromatic amines (HAs) and polycyclic aromatic hydrocarbons (PAHs) in grilled muscle foods - Pinto, Edgar (2021)
Diet contains almost all the necessary ingredients to support the human life. However, chemicals that had a deleterious effect may also be present. Such chemicals can occur naturally in the food, others are synthetic and some are produced during cooking. Cooking toxicants have been receiving special attention in the last decades concerning their formation, occurrence, mitigation, and the impact on human health. The risk of exposure to these compounds depends on the kind of diet, eating habits and cooking practices.